The assessment of indoor environment quality in New Zealand early childhood education centres : a thesis presented in full fulfilment of the requirements for the degree of Master of Philosophy in Building Science at Massey University, Albany, New Zealand - Flood, Tiffany (Massey University, 2019)
The review of literature highlighted a knowledge research gap in the understanding of New Zealand early childhood education indoor environment quality, particularly in Auckland. The objective of this thesis was to, therefore, begin to fill this gap. This was achieved by predominantly monitoring the indoor environment quality in four early learning education centres for one year. The results showed a lack of indoor environment quality standards in early childhood education. Mean carbon dioxide levels in 75% of the sleep rooms monitored exceeded ASHRAE and Ministry of Education school guidelines; the mechanical ventilation in one of the centres did not meet the New Zealand mechanical ventilation standard and the thermal comfort range was exceed 14% of the time during operating hours. The maximum relative humidity guideline set by ASHRAE and recommended in New Zealand schools, was exceeded 29% of the time during operating hours and 66% of the time outside operating hours, therefore possibly supporting mould and bacterial growth. Building audits identified poor cleaning routines in most rooms. Only 22% of the classrooms met the New Zealand building code G7 for Natural light and 55% had poor views to outside, as also required under G7. None of the classrooms achieved a daylight factor greater than 2% as set out in the Ministry of Education school guidelines and 33% of the classrooms interior lighting met New Zealand interior and workplace lighting standards. Those classrooms with mostly hard floors and ceilings have potential reverberation issues. This study highlighted that further research is needed to investigate the ventilation requirements in sleep rooms and the natural light, views to outside and interior lighting requirements within early childhood classrooms. The Ministry of Education and Ministry of Health should provide guidance and advice before a centre is built. The inclusion of an indoor environment quality assessment should be considered as part of a centre’s Education Review Office assessment and that the importance of indoor environment quality should be part of the curriculum when training early learning teachers. This study may be applicable to the New Zealand early childhood education industry and researchers of indoor environment quality.
Figures are re-used with permission.
Keywords: Nursery school facilities; Heating and ventilation; New Zealand; Auckland; Evaluation; Lighting; School buildings; Acoustics; Indoor air pollution; Buildings; Environmental engineering; indoor environment quality; indoor air quality; sound, acoustics; noise; light; early childhood centres; daycare centres; 330206 Building science, technologies and systems